Health behaviors of nursing staff in the use of preventive programs, coping with stress and the impact of additional workload - Sternal, Danuta; Studencka, Agata; Bąk, Ewelina (Journal of Education, Health and Sport, 2023)
Introduction Health behaviors play an important role in preserving, maintaining and improving health. These are actions and behaviors selected by humans, which, based on specific knowledge, remain in a significant relationship with health. Nursing staff, due to their knowledge, skills and duties enshrined in the Act on the Professions of Nurses and Midwives, through their own model of behavior and actions, should encourage appropriate health attitudes. Aim of the study The aim of the study was to learn about selected health behaviors in the use of preventive programs, coping with stress and the impact of additional workload among the nursing staff employed at the Railway Hospital in Wilkowice. Material and methods: The research was carried out using the diagnostic survey method and a standardized scale - Juczyński’s Health Behavior Inventory on a group of 100 nurses. Results: The group of surveyed nurses was characterized by the highest health behaviors in terms of positive mental attitude and proper eating habits, lower in terms of preventive behaviors and health practices. Only 63% of the respondents used prevention programmes. In addition, it was observed that abnormal health behaviors were more common among nurses working additionally in another health care facility. Conclusions: The surveyed nurses used preventive programs on average and manifested health practices at an average level, which was influenced by the burden of additional work. They chose various ways of coping with stress, which were not always pro-health, therefore postgraduate education should emphasize the development of these skills, and nurses should be able to use psychologists employed in hospitals.